Development and application of an indirect ELISA to detect antibodies to Neospora caninum in cattle based on a chimeric protein rSRS2-SAG1-GRA7 - Yang, Cong-Shan; Yang, Chuan-Yin; Ayanniyi, Olalekan-Opeyemi; Chen, Ya-Qian; Lu, Zhen-Xiao; Zhang, Jin-Yi; Liu, Lu-Yao; Hong, Yu-Hang; Cheng, Rong-Rong; Zhang, Xiang; Zong, Qin-Qin; Zhao, Hong-Xi; et al. (Frontiers in Veterinary Science, 2022)
Neospora caninum is an important apicomplexan parasite causing neosporosis in cattle. The disease is recognized as one of the most important cause of reproductive problems and abortion in cattle worldwide. In this context, we developed an indirect enzyme-linked immunosorbent assays (ELISA) with chimeric protein rSRS2-SAG1-GRA7 to diagnose antibodies to Neospora-infection. This indirect ELISA was compared to indirect fluorescent antibody test (IFAT) and western blotting (WB), and the sensitivity and specificity results of ELISA were calculated to be 86.7% and 96.1%, respectively. The overall coincidence rate was 92.6% using IFAT and WB. Additionally, 329 aborting dairy cattle serum samples were tested using this ELISA to evaluate the prevalence of N. caninum in Ningxia, China. The positive rate of N. caninum in these farms was from 19.05 to 57.89%, and the mean rate was 41.64% (±11.01%), indicating that infection with N. caninum may be one of the important causes of cattle abortion in this region. This established rSRS2-SAG1-GRA7 indirect ELISA is capable for detecting the antibodies against N. caninum, and it could be a useful screening tool for monitoring the epidemiology of neosporosis in cattle.